Collateral Binding Principles in Sharia Banking Financing Agreements - Fauzi, Wetria; Agustin Wulandari, Ratih (Sharia and Law Faculty, 2023)
Sharia Banking is based on these sharia principles, all operational activities must not conflict with sharia principles, including financing. The Financing has an important role in the development of Islamic banking. This is to anticipate various risks in bank financing to apply the obligation to provide collateral by customers. The binding of collateral must be clearly regulated and based on sharia principles to achieve sharia compliance. The purpose of this research is to find out and analyze the arrangement of binding collateral in Islamic banking financing, as well as the fulfillment of sharia principles in binding collateral in Islamic banking financing. This is a normative research whose subject matter is the rule of law, legal doctrine to answer certain legal issues. This study concludes that kafalah and rahn are guarantees in the concept of Islamic law, regulated by the DSN-MUI Fatwa Number: 11/DSNMUI/IV/2000 concerning Kafalah. Fatwa Number: 25/DSN/MUI/III/2022 concerning Rahn, Fatwa Number: 92/ DSNMUI/IV/2014 concerning Funding accompanied by Rahn (Al-Tamwil Al-Mautsuq Bi Al-Rahn). However, it has not been set forth in laws and OJK regulations, so that the collateral binding arrangements for Islamic banking use conventional banking guarantee institutions, namely. Pledges, mortgages, fiduciaries, mortgages and warehouse receipts. Not all substances in conventional guarantee institutions can be applied to Islamic banking which prioritizes Islamic principles, namely the values of justice, expediency, balance and universality and does not carry out business activities that contain elements of usury, maisir, gharar, unlawful and unjust, and most importantly overrides the tabbaru principle in Islam. Perbankan Syariah berdasarkan kepada prinsip syariah, seluruh kegiatan operasionalnya tidak boleh bertentangan dengan prinsip syariah termasuk pembiayaan. Pembiayaan mempunyai peranan yang penting dalam perkembangan Perbankan Syariah. Untuk mengantisipasi berbagai resiko dalam pembiayaan, bank menerapkan kewajiban memberikan agunan oleh nasabah. Pengikatan agunan tentunya harus diatur secara jelas dan berdasarkan prinsip syariah untuk mewujudkan syariah compliance. Tujuan penelitian untuk mengetahui dan menganalisis pengaturan pengikatan agunan pada pembiayaan Perbankan Syariah, serta pemenuhan prinsip-prinsip syariah dalam pengikatan agunan pada pembiayaan Perbankan Syariah. Penelitian ini merupakan penelitian normatif yang pokok kajiannya adalah aturan hukum, doktrin hukum untuk menjawab isu hukum tertentu. Penelitian ini menyimpulkan kafalah dan rahn merupakan jaminan dalam konsep hukum Islam, yang diatur pada Fatwa DSN-MUI Nomor : 11/DSNMUI/IV/2000 tentang Kafalah. Fatwa DSN-MUI Nomor : 25/DSN/MUI/III/2022 tentang Rahn, Fatwa DSN-MUI Nomor : 68/DSN-MUI/III/2008 tentang Rahn Tasjily diperbolehkan adanya jaminan barang., Fatwa DSN-MUI Nomor : 92/DSNMUI/IV/2014 tentang Pembiayaan yang disertai Rahn (Al-Tamwil Al-Mautsuq Bi Al-Rahn). Namun belum dituangkan dalam peraturan perundang-undangan ataupun peraturan Otoritas Jasa Keuangan, sehingga pengaturan pengikatan agunan pada Perbankan Syariah menggunakan lembaga jaminan perbankan konvensional yaitu ; gadai, hipotik, fidusia, hak tanggungan, dan resi gudang. Tidak semua subtansi pada lembaga jaminan konvensional dapat diberlakukan pada Perbankan Syariah yang mengutamakan pinsip-prinsip keislaman yaitu; nilai-nilai keadilan, kemanfaatan, keseimbangan, dan keuniversalan (rahmatan lil ‘alamin) serta tidak melakukan kegiatan usaha yang mengandung unsur riba, maisir, gharar, haram dan zalim, serta yang paling utama mengesampingkan prinsip tabbaru dalam islam.